Study of Learning Strategies and Cognitive Capacities in Hearing and Non-hearing Pupils. (21st February 2017) - Antoñanzas, José Luis; Lorente, R.
Abstract: One very important matter in hearing-impaired pupils is to know whether they use different learning strategies to hearing pupils students. Similarly, knowing if they have the same cognitive capacities as their hearing peers is also interesting. Research was done to compare the cognitive capacities of hearing-impaired pupils to hearing pupils in years 4, 5 and 6 of primary education with the TEA1 test. In parallel, use of learning strategies by both pupil types was studied. The study sample was formed by 223 pupils aged between 9 and 12 years (distributed in the above three primary education years). The results barely showed any differences in cognitive capacities, but a significant difference was observed in study habits and using certain strategies between students with and without hearing impairments.